Optimizing maleic anhydride content to enhance mechanical performance and thermal stability of recycled polyolefin blends - Choi, Sungwoong; Jang, Seongeun; Do, Garam; Lee, Patrick C.; Choi, Duyoung (Nature Publishing Group, 2026)
This study evaluated the effects of maleic anhydride (MA) coupling agent on the mechanical and thermal properties and long-term stability of post-consumer recycled (PCR) plastics. The addition of MA coupling agent increased the tensile strength by 32.12%, enhancing the mechanical durability of the recycled plastic. Furthermore, the melt index (MI) increased by 366.23%, significantly improving processability. Thermogravimetric analysis (TGA) results showed a significant improvement in thermal stability, and a lifetime prediction model estimated an extension of the material’s life by 532.66% at 200 °C. These results demonstrate that MA coupling agent effectively suppresses long-term degradation at high temperatures. Therefore, MA coupling agents can simultaneously improve mechanical properties and recyclability and offer a potent solution for creating sustainable plastics within a circular economy.